Streamflow alterations, attributions, and implications in extended East Rapti Watershed, central-southern Nepal - Pandey, Vishnu Prasad; Shrestha, Dibesh; Adhikari, M.; Shakya, S. (MDPI, 2020)
Streamflow alteration and subsequent change in long-term average, seasonality, and extremes (e.g., floods and droughts) may affect water security, which is a major concern in many watersheds across the globe. Both climatic and anthropogenic activities may contribute to such changes. Therefore, this study assesses: (i) Streamflow and precipitation trends to identify streamflow alterations in the Extended East Rapti (EER) watershed in central-southern Nepal; (ii) relationship of the alterations to climatic and anthropogenic sources; and (iii) implications of streamflow changes to the socio-environmental system. The trends in streamflow were analyzed for pre-and post-1990 periods considering the abrupt shift in temperature trend in 1990. Results showed a general decreasing trends in discharge post-1990 in the EER watershed. Human activities have significantly contributed in altering streamflow in the EER. Human-induced streamflow alterations have affected the water availability, food security, river health, aquatic biodiversity, and groundwater abstraction in the EER watershed.